A systematic method for mapping customer requirements to quality characteristics in product lifecycle. (17th December 2007) - Wang, M-Q.; Ma, Y-S.
This paper presents a fundamental research on customer requirements modelling and propagation throughout the whole product development lifecycle. A theoretical mapping model, from customer requirements to quality characteristics, is established. It covers three processes, i.e., the qualification and classification of customer requirements, the generation and transformation of product quality characteristics, and product quality characteristics optimisation. The Analytic Network Process (ANP) approach was adopted to establish the weights of different customer requirements and product quality characteristics. Intra- and inter-relations for customer requirements and quality characteristics are modelled. Matching and conflict-resolving algorithms are proposed. A case study is also given.